Achievements, history and challenges in geophysics : 60th Anniversary of the Institute of Geophysics, Polish Academy of Sciences - Majdański, Mariusz; Moskalik, Mateusz; Bialik, Robert (GeoPlanet: Earth and Planetary Sciences, 2014)
Over the last six decades, the field of geophysics has experienced rapid development. Seismic methods, magnetic studies, hydrology and atmospheric sciences have expanded thanks to a boom in the computer sciences and measurement techniques. The frontiers of geophysics have also expanded, now including research on the polar areas, both Arctic and Antarctic. All these events are clearly reflected in the 60-year-long history of the Institute of Geophysics, Polish Academy of Sciences. This volume describes the most prominent achievements, the history of research and also the future potential of the Institute of Geophysics PAS. It describes measurements in various projects, methods of interpreting scientific data, and last but not least the people who have driven this research in many scientific projects.